Tribal Legal System, Social Order and Conflict Resolution: A Case of Provincially Administered Tribal Areas of Pakistan - Shafiq, Muhammad; Khan, Ashfaq Ahmad; Waseem, Liaqat Ali; Bakhsh, Noor (Journal of History Culture and Art Research, 2017)
This paper aims to explore the importance of kinship system in tribal areas (Fazla Kach) of province Punjab, Pakistan. An exploratory research was conducted by using the qualitative research tools for data collection including key informant interviewing and participant observation as the major tools for data collection. It was revealed through data analysis that kinship system plays a central role in tribal life. Kinship system merely serves as the code of tribal life of Buzdar tribe of Fazla Kach, Punjab Pakistan. Extended family system is lead and identified by the grandfather’s name who possesses the ultimate decision-making power. Kinship system plays a pivotal role to maintain social order through repressive tribal laws which are executed through Meal-Maraka (indigenous conflict resolution body). Each minimal lineage is represented by Sofaid Rish (white bearded). Furthermore, data revealed that segmentary lineage kinship is decisive in formal electoral process. Ritual and ceremonies, property inheritance, communal land holding and sheep flock herding and conflict resolution are conducted via patriarchal kinship system. Females are very active in daily chores of life yet are invisible in socio-political and economic system of the tribe.